Regionalidade, características do gestor, aspectos do fundo e fatores macroeconômicos: o que influencia a captação líquida de fundos de investimento brasileiros - Tavares, Vitor Borges (2023)
Contextualization The Brazilian fund market is one of the largest in the world, with net assets exceeding R$7 trillion. The movement of this amount is the result of investments and redemptions from investors. In this context, research has focused mainly on rational aspects to explain the entry and exit of resources, such as previous performance, age and size of the fund, charging of management and performance fees, in addition to macroeconomic factors, such as GDP, rate interest and exchange rates. However, investors have different abilities to analyze the fundamentals for making investment decisions, given the existence of particularities in accessing and processing information and decision making at the individual level. In this sense, professional/qualified investors and ordinary investors are different populations in the Brazilian fund market, so that retail fund investors are less sophisticated than qualified/professional investors. However, evidence suggests that investors who invest in funds from large Brazilian banks have different behavior, in some aspects, in relation to those who invest in funds from other financial institutions. As Brazilian financial education is relatively low, the population's banking experience is significant and banks have diverse investment options, it is likely that the investment of resources in funds from the largest banks will be more sensitive to past performance, to the detriment of the use of benchmarks more complex. Furthermore, this research argues that the location of the manager influences the net inflow of investment funds. Regionality has a relevant influence on the availability and obtaining of data and information. Therefore, it is important both for the relationship between investors and fund managers and for managers of funds and investment assets. Furthermore, in large cities, there are a greater number of institutional investors with better conditions for obtaining and processing information and monitoring the performance of investment decisions. Furthermore, in less developed regions, there is a greater prevalence of familiarity bias in investment decisions. Therefore, the thesis is defended that the net inflow of investment funds is affected by the fund's restriction to qualified/professional investors, the type of institution of the fund manager and regionality. Objective The present study aimed to analyze how the net inflow of investment funds is affected by the fund's restriction to qualified/professional investors, the type of institution of the fund manager and regionality. It also had the following specific objectives: 1) test differences in the influence of explanatory factors on net fundraising, considering the thesis defended; and 2) develop a predictive model for the net inflow of investment funds. Method In general, this research used quarterly data on net inflows and factors that explain the flow of resources from investment funds, from 2011 to 2022. Multiple linear regressions were estimated to test differences between regions, between funds managed by the largest banks and funds not managed by the largest banks and between retail funds and funds exclusive to qualified/professional investors. To compare regional performance in net fundraising, difference between means tests were carried out. And finally, an artificial neural network model was developed to predict the net inflow of equity funds. Results The main results found in this research concern differences in the impact of predictive factors on the net inflow of investment funds according to the fund grouping perspective analyzed. It was found that the same variation in the fund's quarterly performance provides net inflow practically ten times higher than multimarket retail funds, compared to funds restricted to qualified and professional investors. When comparing these groups, the differences in this relationship were also statistically clear and economically important in equity and fixed income funds, always in the sense that previous good performance provides greater inflow of resources into retail funds. Similarly, it was found that the positive net inflow of multimarket and fixed income funds from the country's largest banks is more dependent on good past performance, compared to funds managed by other institutions. In equity funds, this difference was not statistically clear. Furthermore, the results showed that, based on the data analyzed, with regard to the influence of macroeconomic factors and variables related to the funds, on decisions to contribute and withdraw resources, investors in bank equity funds do not act differently of other investors. Regarding the effects of regionality, with regard to the explanation of net uptake, important and statistically clear differences were verified in specific regions and time. Finally, the developed neural network model achieved considerable success in predicting data without supervisory bias. Compliance of the research with the PPGAdm concentration area (Regionality and Management) and with the research line The research highlighted important differences from a practical/economic point of view in the net raising of investment funds according to regional aspects and characteristics of fund managers. Thus, the study adheres to the area of concentration of Regionality and Management, as it presents circumstantial and economic particularities between regions, providing subsidies for local developments. However, results from the funds in the region of influence of the Federal University of Uberlândia/MG were presented and analyzed, contributing to expanding knowledge of this market in the region. Impact and innovative character in intellectual production This research fills the gap on regional influence on decisions regarding the flow of fund resources in Brazil. As a consequence, it contributes to studies on the subject that, until then, ignored the effects of regionality in understanding the movement of capital invested in funds in the country. Furthermore, it shows important evidence about differences in net inflow between funds managed by the country's largest banks and funds managed by other institutions. By shedding light on these differences, it provides support for new research on fund fundraising and presents the need to analyze previous research with caution, as the results found may not represent the reality of certain groups of funds. Economic, social and regional impact The results found in the research contribute to a better understanding of the movement of resources in a market worth more than R$7 trillion. Thus, it provides support for the implementation of personalized strategies by fund managers, including at the regional level. Furthermore, investors' decisions represent an internal driver that directly affects the development of the financial market. Thus, by providing evidence on decision making, the study can contribute to improving investment decisions and investor performance and encouraging investment. Regional implications With the decision of the Federal Supreme Court regarding article 1 of Complementary Law 157/2016, taxation of investment fund management services remains the responsibility of the entity where the fund manager is based. Therefore, the results of this research are interesting to municipalities, as they will have subsidies to implement tax collection strategies to promote the funds market in the municipality.